INTEREST IN LEARNING BY USING VISUAL MEDIA IN SOCIAL STUDIES SUBJECTS - NORLELA, NOR LELA (JURNAL SOCIUS, 2023)
The purpose of this study was to find out students' interest in learning by using visual media in social studies subjects in Class VIII of SMP Negeri 4 Sampit for the 2021/2022 academic year. This study uses a qualitative approach. The research subjects in this study were 3 (tree) grade VIII students of SMP Negeri 4 Sampit who were taken by one representative from 3 classes while the informants were social studies teachers who taught 3 (three) grade VIII students. Data collection techniques using observation, interviews and documentation. The results of the study concluded that the use of visual media in the social studies learning process can increase student learning interest as seen from students paying more attention when the teacher explains learning material, feelings of pleasure, interest in the material because it is not boring and fosters curiosity, and satisfaction when learning social studies using Visual media can improve understanding and memory of learning material besides that in terms of student satisfaction they feel quite satisfied learning social studies using visual media because of the importance of innovation and creativity of social studies teachers in designing and making visual learning media so that they can help achieve social studies learning goals.